PENGARUH LINGKUNGAN KELUARGA DAN DISIPLIN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 10 KOTA JAMBI - Kasiono, Febri Adriansyah, (SJEE (Scientific Journals of Economic Education), 2017)
This study aims to determine the description of the family environment and discipline of student learning outcomes, and the influence of family environment and discipline on learning outcomes in SMA Negeri 10 Kota Jambi. The results showed that the achievement of family environment respondents including good enough category with a value of 79.45%, discipline including good enough category with a value of 80.31% and learning outcomes of 41.21% obtained value above KKM .. Meanwhile, the magnitude of the influence of family environment and discipline on the learning outcomes in SMA Negeri 10 Kota Jambi can be made a regression equation that is Y = a + X1 + X2 = 70,552 + 0,293 + 0,260. And, for t arithmetic X1 = 4.738, and t arithmetic X2 = 3.652 then thitung> ttabel.Kata Kunci : Family Environment, Discipline